Multivariate Extension Principle and Algebraic Operations of Intuitionistic Fuzzy Sets - Yonghong Shen; Wei Chen (Journal of Applied Mathematics)
This paper mainly focuses on multivariate extension of the extension principle of IFSs. Based on the Cartesian product over IFSs, the multivariate extension principle of IFSs is established. Furthermore, three kinds of representation of this principle are provided. Finally, a general framework of the algebraic operation between IFSs is given by using the multivariate extension principle.